2010
DOI: 10.1227/neu.0b013e3181eff6f7
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Radiosurgery for Dural Arteriovenous Fistulas

Abstract: Gamma Knife radiosurgery is an effective adjunct therapy for dAVFs with persistence of flow after open neurosurgical resection or endovascular treatment while still maintaining a role in nonaggressive dAVFs not amenable to either surgery or embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 23 publications
1
54
1
Order By: Relevance
“…Factors found by the included studies to be significantly associated with obliteration are as follows: CS DAVFs, Borden Type I DAVFs, DAVFs without CVD, hemorrhage at presentation, target volume < 1.5 ml, and Cognard Types III or IV DAVFs. 7,16,51 Factors found to be nonsignificant are as follows: patient age and sex, prior treatments, DAVF location and size, DAVFs with multiple arteriovenous connections versus DAVFs with single arteriovenous connections, and minimal radiation dose delivered to DAVFs. number of other studies have investigated the use of SRS for treating DAVFs in other locations, with variable rates of success.…”
Section: Outcomes For Davfs With Cvd Versus Davfs Without Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors found by the included studies to be significantly associated with obliteration are as follows: CS DAVFs, Borden Type I DAVFs, DAVFs without CVD, hemorrhage at presentation, target volume < 1.5 ml, and Cognard Types III or IV DAVFs. 7,16,51 Factors found to be nonsignificant are as follows: patient age and sex, prior treatments, DAVF location and size, DAVFs with multiple arteriovenous connections versus DAVFs with single arteriovenous connections, and minimal radiation dose delivered to DAVFs. number of other studies have investigated the use of SRS for treating DAVFs in other locations, with variable rates of success.…”
Section: Outcomes For Davfs With Cvd Versus Davfs Without Cvdmentioning
confidence: 99%
“…7,12,22,23,35,39,51 Although endovascular embolization may provide immediate symptomatic relief and reduction of hemorrhage risk, the treatment may not afford longterm cure in cases of subtotal obliteration or delayed recanalization. 24 Therefore, SRS serves as a complementary treatment by potentially increasing the likelihood of permanent DAVF occlusion.…”
mentioning
confidence: 99%
“…7 In this study, the obliteration rate was 75% for DAVFs smaller than or equal to 10 mm, decreasing to 64% for those larger than 10 mm. Indeed, this study concluded that the 2 main statistically significant factors negatively influencing DAVF obliteration were CVD and target size greater than 20 mm.…”
mentioning
confidence: 48%
“…Although one study did not demonstrate a significant difference in obliteration rates for SRS in conjunction with embolization, 7 another demonstrated greater obliteration rates when these 2 modalities were used in conjunction.…”
Section: 35mentioning
confidence: 90%
“…In the largest series by Cifarelli et al, 3 55 adults with dural AVFs were treated with GKS from 1989 to 2005 and angiographic obliteration was achieved in 54%-65% at 3 years. However, 5% of patients experienced a hemorrhage during the latency period from treatment to obliteration.…”
Section: Stereotactic Radiosurgerymentioning
confidence: 99%